Governing Complex Societies - Pierre, J. author. aut Link
VI, 158 p.
Keywords: Western societies are becoming increasingly complex and challenging to govern, yet the modern state continues to play a central role in governance. This book presents a detailed analysis of the challenges confronting the contemporary state and the processes through which the state addresses those challenges. The notion of 'governing without government' is critiqued; instead, Pierre and Peters argue that what is happening a more a matter of state transformation than state decline.